2016
DOI: 10.1016/j.actamat.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Microalloying for the controllable delay of precipitate formation in metal alloys

Abstract: A model is presented to predict the effectiveness of dilute solutes in delaying precipitate formation, with application to natural and artificial aging in metal alloys. Control of aging is achieved via the binding, at natural aging temperatures, and release, at artificial aging temperatures, of excess quenched vacancies by the solute atoms. The binding of vacancies to the solute atoms reduces the vacancy concentration in the bulk lattice, and thus reduces the rate of transport processes that control aging. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
(32 reference statements)
4
17
0
Order By: Relevance
“…Aggregates of a few solute atoms that can act as vacancy traps [34] would thus slow vacancy-mediated solute diffusion that is necessary to form larger precipitates, greatly affecting the aging times. This conclusion of dominance of diffusion-controlled aging is also consistent with recent findings that the addition of 100 ppm of Sn to Al-6061 can significantly delay aging, attributed to trapping of the quenched-in vacancies by the Sn atoms [11,35]. Our results thus point toward the need for a systematic study of the energetics of aggregates in the GP-zone regime, and the interactions between those aggregates and vacancies and/or trace elements in the alloy to understand and fine-tune the behavior of Al-6000 alloys in the early stages of precipitation.…”
Section: Resultssupporting
confidence: 91%
“…Aggregates of a few solute atoms that can act as vacancy traps [34] would thus slow vacancy-mediated solute diffusion that is necessary to form larger precipitates, greatly affecting the aging times. This conclusion of dominance of diffusion-controlled aging is also consistent with recent findings that the addition of 100 ppm of Sn to Al-6061 can significantly delay aging, attributed to trapping of the quenched-in vacancies by the Sn atoms [11,35]. Our results thus point toward the need for a systematic study of the energetics of aggregates in the GP-zone regime, and the interactions between those aggregates and vacancies and/or trace elements in the alloy to understand and fine-tune the behavior of Al-6000 alloys in the early stages of precipitation.…”
Section: Resultssupporting
confidence: 91%
“…In metals, most solutes forming precipitates are substitutional and thus the diffusion mechanisms involve mainly the movement of vacancies. Therefore, the precipitation kinetics is directly controlled by the concentration of vacancies by their diffusion rate within the material and by their interaction with solutes [96][97][98]36,99,100]. An important exception is the precipitation of cementite in steels during martensite tempering, where carbon diffuses interstitially.…”
Section: Influence Of the Diffusion Mechanisms On Precipitation Kineticsmentioning
confidence: 99%
“…But the problem arises during the transportation period, during which the formability of the alloy decreases due to an increase in hardness as a result of natural aging. [22][23][24] So, there is a demand for stable formability of this alloy during the transportation stage to the processing stage. Studies 13,22,24 have shown Sn as a potential microalloying element in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] So, there is a demand for stable formability of this alloy during the transportation stage to the processing stage. Studies 13,22,24 have shown Sn as a potential microalloying element in this regard.…”
Section: Introductionmentioning
confidence: 99%